The impact of motivation on academic performance: evidence from Malaysian university student-athletes / Muhammad Azwan Mohd Azmi and Radzliyana Radzuwan - Mohd Azmi, Muhammad Azwan; Radzuwan, Radzliyana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Balancing sports and academics present challenges for student-athletes, potentially affecting their motivation and academic performance. Prior research suggests that time constraints and physical fatigue negatively impact academic success [1]. Motivation, influenced by intrinsic and extrinsic factors, plays a crucial role [2]. Institutional support, such as mentorship and flexible scheduling, may enhance academic outcomes [3]. This study examines these relationships among KARiSMA Negeri Sembilan 2024 FSR student-athletes at UiTM Seremban. A quantitative, non-experimental survey design was adopted, using purposive sampling. Data were collected via the Academic Motivation Scale (AMS-28) [4] with 28 items and the Academic Success Inventory for College Students (ASICS) [5] with 48 items. Responses from 83 student-athletes were analyzed using Jamovi version 2, employing descriptive (mean and standard deviation) and inferential statistical methods (Pearson Correlation and Independent t-Tests).